(3RHOI GdCNHGQs - (3eMeO MSjf Hf ceGd GdOjf GdSHQhGRjs
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi GdZfi eMeO MSjf Hf ceGd GdOjf GdSHRhGQi gPG cJGH MQQJ ajg fHPkG ef GdCNHGQ GdeCKhQI Yf GdCFeI GdCWgGQ s
(3BNQgG (B:s
(3hcGf CTO GdfGS YPGHkG jhe GdbjGeI ROfGge YPGHkG ahb GdYPGH gPG BNQ eG GfJNHJ ef GdJhQjI hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs